117k views
4 votes
Why does 3-(x+1)=3-x-1? Use the distributive property.

User Ong
by
5.8k points

2 Answers

4 votes

3-1(x+1) = 3-x-1

Step 1. distribute the negative sign

2(-x-1) = 3-x-1

Step 2. distribute the 3

-2x-3= 3-x-1

add 3 on both sides

-2x = 6 - x - 1

add x to both sides

-1x = 6 - 1

-1x=5

x=5

SO..... u have to plug 5 in

User Qvpham
by
5.6k points
1 vote


3-(x+1)=3-x-1


(+3)-(x+1)


(+3)-1(x+1)

Distribute the -1 to (x+1)


(+3)-1x-1


3-x-1


-x+2

User Andrew Barnett
by
5.9k points